1979
DOI: 10.1042/bj1820617
|View full text |Cite
|
Sign up to set email alerts
|

An active-site-directed adenosine triphosphate analogue binds to the β-subunits of factor F1 mitochondrial adenosine triphosphatase with its triphosphate moiety

Abstract: The reaction of the mixed anhydride of [3H]ATP and mesitylenecarboxylic acid and soluble mitochondrial adenosine triphosphatase is accompanied by the covalent binding of one molecule of the inhibitor to a molecule of the enzyme and results in the inhibition of adenosine triphosphatase activity by more than 90%. The electrophoresis of adenosine triphosphatase modified by reaction with the mixed anhydride of [3H]ATP and mesitylenecarboxylic acid in polyacrylamide gel in the presence of sodium dodecyl sulphate sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…As noted before, the essential tyrosyl and glutamyl residues are conserved in homologous regions of sequence in beef heart Flfi subunit and E. coli Flfl subunit, and they are also conserved in chloroplast Flfl subunit (Zurawski et al, 1982). Two other ATP analogs with reactive substituents in position approximating that of the fl-7 phosphoryl groups of ATP have been shown to inhibit soluble F~ activity and to covalently label the fl subunit (Budker et al, 1977;Drutsa et al, 1979). The inhibitory, reactive analog of Pi(4-azido,2-nitrophenylphosphate) has also been shown to label the fl subunit (Lauquin et al, 1980).…”
Section: Mechanism Of Atp Synthesis and Hydrolysis On F1mentioning
confidence: 94%
“…As noted before, the essential tyrosyl and glutamyl residues are conserved in homologous regions of sequence in beef heart Flfi subunit and E. coli Flfl subunit, and they are also conserved in chloroplast Flfl subunit (Zurawski et al, 1982). Two other ATP analogs with reactive substituents in position approximating that of the fl-7 phosphoryl groups of ATP have been shown to inhibit soluble F~ activity and to covalently label the fl subunit (Budker et al, 1977;Drutsa et al, 1979). The inhibitory, reactive analog of Pi(4-azido,2-nitrophenylphosphate) has also been shown to label the fl subunit (Lauquin et al, 1980).…”
Section: Mechanism Of Atp Synthesis and Hydrolysis On F1mentioning
confidence: 94%
“…Careful chemical determinations showed that dial ATP has a tendency to lose its triphosphate group and to generate an adenine containing compound with a highly reactive conjugated aldehyde group, ex plaining the formation of the stable conjugated Schiff base with FI (218, 219). An etheno derivative of dial ATP (dial e-ATP) has been reported to inactivate beef liver F" with full inactivation being attained for 1 mol reagent bound per mol F, at the level of the 13 subunit Two other affinity labels have been used with mitochondrial F" namely the mixed anhydride formed by condensation of ATP and mesitylene carboxylic acid (222) and the A TP -'Y-4(N -2-chloroethy I-N -methy lamino) benzoy lamidate (223). In the presence of Mg 2 + , dial ATP was hydrolyzed to give dial-ADP, indicating that dial ATP binds at the active site of F ,.…”
Section: Affinity Labelsmentioning
confidence: 99%
“…An adenine nucleotide binding site appears to be present in each of the 3ca-and 3(3-subunits, making six in all (Slater et al, 1979;Wagenvoord et al, 1980). Covalent modification experiments indicate that ( contributes to catalysis (Ferguson et al, 1975;Esch and Allison, 1978;Drutsa et at., 1979;Yoshida et al, 1981a, 198 lb); also it is able to bind both ADP and ATP as required for catalysis (Harris, 1978;Wagenvoord et al, 1980). Also, ATP binds to isolated ca-subunits with high affinity, thereby causing a large conformational change in the protein (Dunn, 1980).…”
Section: Introductionmentioning
confidence: 99%